Children, time allocation and consumption insurance - Richard Blundell; Luigi Pistaferri; Itay Saporta-Eksten (Institute for Fiscal Studies (IFS), 2015)
We consider the life-cycle problem of a household that in each period decides how much to consume and how to allocate spouses' time to work, leisure, and childcare. In an environment with uncertainty, the allocation of goods and time over the life cycle plays the further role of providing insurance against shocks. We use longitudinal data on consumption, and husband and wife separate information on hourly wages, hours of work, and time spent with children to estimate structural parameters measuring the sensitivity of consumption and time allocation choices to transitory and permanent wage shocks. These structural parameters provide a full picture regarding the ability of household to smooth marginal utility in response to shocks. In addition, information on hours of work and hours spent on childcare allows to decompose overall Frisch response into two components, one reflecting the degree of complementarity between husband's and wife's leisure ("companionship" or "love") and another reflecting the degree of substitutability of their childcare time in the production of childcare services.
Keywords: 330